Strategi Algoritmik Sistematis untuk Pemecahan Masalah Jarak dan Sudut pada Materi Dimensi Tiga: Strategi Algoritmik Sistematis untuk Pemecahan Masalah Jarak dan Sudut pada Materi Dimensi Tiga - Suhardiman Darson Tamu; Nosva Adam Yunus; Febiyanti R. Hasan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Three-dimensional material, particularly the topic of distance and angles between geometric elements, is one of the most difficult parts for high school students because it requires high visualization and spatial reasoning skills. This study aims to develop a systematic algorithmic strategy to solve distance and angle problems in three-dimensional space in a more structured and student-friendly manner. The research approach used is qualitative-descriptive with analysis of textbooks, curriculum documents, and empirical experiences in teaching spatial geometry. The results of the study produced two main algorithms, namely the distance algorithm and the angle algorithm, each of which is arranged in logical steps starting from translating the problem into a drawing, identifying auxiliary triangles, analyzing the types of triangles, to applying relevant trigonometric theorems such as Pythagoras and the cosine rule. This strategy has been proven to strengthen the connection between students' conceptual understanding and procedural skills in solving problems. The systematic application of algorithms helps students build spatial visualization skills, improve thinking efficiency, and foster algorithmic thinking patterns in mathematics learning.